Musical hallucinations: a rare and atypical presentation of anti-IgLON5 disease responsive to immunosuppressive therapy. Issue 2 (18th February 2021) - Stoyanov, Alex; McDougall, Alan; Urriola, Nicolas
Abstract : IgLON5 antibodies are typically associated with the insidious onset of sleep disorder, parasomnia, gait disturbance and abnormal movements, with variable response to immunosuppressive therapy. We describe a case of a 50-year-old man who presented with acute speech difficulties, headache and focal seizures followed by well-formed visual hallucinations, and later, musical hallucinations of mainstream popular music. MRI of the brain demonstrated right temporal lobe changes with corresponding epileptiform activity seen on electroencephalogram. Subsequently, IgLON5 antibodies were detected in the serum. The patient was treated with anticonvulsants, as well as azathioprine with a tapering oral prednisone course with a complete resolution of the symptoms. Our case demonstrates an unusual presentation of the rare but increasingly described anti-IgLON5 disease, with musical hallucinations. The case highlights the variable and evolving clinical phenotypes that can be seen in autoimmune central nervous system disorders.